Mapping Uganda's coffee quality - Asten, Piet J.A. van; Mukasa, D.; Jassogne, Laurence T.P.; Nakendo, S.; Kananura, E. (2013)
This report is a first step in a joint attempt to map Uganda's coffee quality at harvest. This report provides a summary overview of the data collected for the most important Arabica and Robusta-growing regions in Uganda. The work is building on the coffee yield mapping led by IITA and supported by USAID through their respective APEP (2007-2008) and LEAD projects (2010-2011). The complementary field work to collect the coffee quality samples was fully covered by aBi-Trust. The evaluation of the coffee was covered by UCDA. In addition, supplementary resource investments in technical staff were made by IITA and NARO's coffee research institute (NaCORI). Coffee quality is receiving increasing attention on the international coffee markets, with significant price differentials for high quality and certified coffee. Whereas this trend was first and foremost observed in Arabica, the Robusta market appears to move in the same direction. In Arabica, the quality grading is commonly referred to as Q-grading system. A similar grading system was only developed recently for Robust, known as the R-grading system. Both approaches have been used in this study. To allow farmers, farmer groups, traders and processors to benefit from the increasing demand for coffee quality and distinct flavour profiles, the research team of IITA and NaCORI revisited the farms that were earlier subject to an on-farm survey that quantified yield, soil fertility, pest and disease pressure, and crop management practices. With help of the private and public secror (a.o. Volcafé, HRNS, UCDA, NUCAFE, and NAADS), samples were collected from mature coffee in farmers fields. These were locally processed (i.e wet processing for Arabica and drying for Robusta) and carefully labelled and stored. Thereafter, UCDA skilfully led the hulling, grading, and cupping of the 371 samples.